The Evolution of E-Sports in Indonesia: Between Opportunities and the Need for Regulation - Supriatna, Rimba (Fakultas Hukum, Universitas Islam Bandung, 2024)
The dynamics of E-Sports rapidly has shown the implication to system of regulation that could possibly arrange the way and the shape E-Sport Industry should be running. Shortly, such as condition will automatically disrupt the legal system. E-Sports in this article, concern on a fundamental set of legal issues as an integral to E-Sports ecosystem which has been more attractive and challenging regarding the strategic impact not only in the field of economical aspect but also the other multidimensional aspect. This expanding industry seems poised to bring in new era of digital economic industry, but it also needs to be aware of the myriad legal concerns.